OPTIMALISASI IMPLEMENTASI PENDIDIKAN INKLUSI BAGI SISWA SEKOLAH DASAR DI KABUPATEN POHUWATO - Furqan, Rahmatul; Dewi, Shabrina Syntha (Jurnal Abdi Insani, 2024)
This digital literacy socialization activity aims to enhance understanding and skills related to inclusive education for teachers and parents in Pohuwato Regency. The full support from the Pohuwato Regency Education Office, the enthusiasm of the participants, and adequate facilities were the main supporting factors in organizing this activity. The participants, consisting of 15 teachers and 10 parents, showed a significant increase in understanding of the basic concepts of inclusive education, effective teaching strategies, and the utilization of technology in inclusive education, as evidenced by the results of the pre-test and post-test, as well as demonstrations and practices during the training.However, several challenges such as the limited training duration, limited access to technology for participants from remote areas, and social stigma towards disabilities still need to be addressed. Nonetheless, the positive attitude change towards inclusive education among the participants indicates the strong impact of this activity.